Hubungan Berat Badan Lahir, Panjang Badan Lahir, dan Riwayat Imunisasi dengan Kejadian Stunting pada Balita di Wilayah Kerja Puskesmas Kopang - Imam Syahrul Fatoni Putra; Lalu Irawan Surasmaji; Herlinawati Herlinawati; Kadek Wini Mardewi (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Stunting is characterized by a short stature based on a length or height-for-age measurement that falls below -2 standard deviations (SD) on the WHO growth chart. It can lead to delays in physical and cognitive development in children. Stunting is influenced by several factors, including birth weight, birth length, and immunization history. This study aims to determine the relationship between birth weight, birth length, and immunization history with the incidence of stunting in children under five in the working area of Kopang Health Center. This analytical observational study used a case-control design with a sample of 100 participants, divided into 50 cases and 50 controls, selected using purposive sampling. The data collected were analyzed using the chi-square test with a significance level of p-value 0.05. Results: Univariate analysis showed that 50 (50%) children experienced stunting, 42 (42%) had low birth weight, 37 (37%) had short birth length, and 55 (55%) did not have a complete immunization history. Bivariate analysis indicated a significant relationship between birth weight and stunting (p-value=0.002; OR=3.930; 95% CI=1.688-9.154), as well as between birth length and stunting (p-value=0.004; OR=3.814; 95% CI=1.610-9.161). No significant relationship was found between immunization history and stunting (p-value=0.108; OR= 2,087; 95% CI= 0,936-4,653). There is a significant relationship between birth weight and birth length with the incidence of stunting. There is no significant relationship between immunization history and stunting.  Keywords: Stunting, Children Under Five, Birth Weight, Birth Length, Immunization History.  ABSTRAK Latar belakang: Stunting adalah perawakan pendek berdasarkan panjang atau tinggi badan menurut usia kurang dari -2 Standar Deviasi (SD) pada kurva pertumbuhan WHO, dapat menyebabkan hambatan dalam fisik dan kognitif anak. Stunting dipengaruhi oleh beberapa faktor seperti berat badan lahir, panjang badan lahir, dan riwayat imunisasi. Tujuan penelitian untuk mengetahui hubungan berat badan lahir, panjang badan lahir, dan riwayat imunisasi dengan kejadian stunting pada balita di wilayah kerja Puskesmas Kopang. Penelitian obsevasional analitik dengan desain penelitian case control. Jumlah sampel sebanyak 100 sampel yang dibagi menjadi 50 sampel sebagai kelompok kasus dan 50 sampel sebagai kelompok kontrol, diambil menggunakan teknik purposive sampling. Data yang diperoleh dianalisis dengan uji chi-square dengan nilai signifikansi p-value 0,05. Hasil penelitian: Hasil analisis bivariat menunjukkan terdapat hubungan signifikan antara berat badan lahir dengan kejadian stunting (p-value= 0,002; OR= 3,930; 95% CI= 1,688-9,154). Didapatkan juga hubungan signifikan antara panjang badan lahir dengan kejadian stunting (p-value= 0,004; OR= 3,814; 95% CI= 1,610-9,161). Namun, tidak terdapat hubungan signifikan antara riwayat imunisasi dengan kejadian stunting (p-value= 0,108; OR= 2,087; 95% CI= 0,936-4,653). Terdapat hubungan yang signifikan antara berat badan lahir dan panjang badan lahir dengan kejadian stunting. Namun, tidak terdapat hubungan yang signifikan antara riwayat imunisasi dengan kejadian stunting.  Kata Kunci: Stunting, Balita, Berat Badan Lahir, Panjang Badan Lahir, Riwayat Imunisasi